PsycEXTRA Dataset 2011
DOI: 10.1037/e578442014-108
|View full text |Cite
|
Sign up to set email alerts
|

Test takers' experiences during adaptive versus fixed item testing

Abstract: of the College Board, graces this issue's cover. This richly detailed visual depicts examinees' reading abilities across the multiple dimensions of a large-scale measure of reading ability. These creative researchers described their work this way. This visual answers the following question: "Based on ex-aminees' performance on 40+ reading items, is it possible to visually identify clusters of examinees that have different reading skills?" The plot answers the question by showing three panels: the outer two vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies have reported that highly anxious students are more likely to perform poorly, even when they work on computer-adaptive tests (Lu et al, 2016;Ortner & Caspers, 2011). Moreover, some found that students felt more anxious when taking a computer-adaptive test than when taking a test in the traditional format (Ortner et al, 2014). Students may feel pressured by personalized problems, which require constant challenge, as they experience almost equal amounts of successes and failures during tests.…”
Section: Computer-adaptive Tests and Preference For Personalized Prob...mentioning
confidence: 99%
“…Some studies have reported that highly anxious students are more likely to perform poorly, even when they work on computer-adaptive tests (Lu et al, 2016;Ortner & Caspers, 2011). Moreover, some found that students felt more anxious when taking a computer-adaptive test than when taking a test in the traditional format (Ortner et al, 2014). Students may feel pressured by personalized problems, which require constant challenge, as they experience almost equal amounts of successes and failures during tests.…”
Section: Computer-adaptive Tests and Preference For Personalized Prob...mentioning
confidence: 99%